ISTIBD?L WAKAF:: KOMPARASI PEMIKIRAN ABU ISH?Q AL-SYAIR?Z? DAN ZAKARIYY? AL-ANSH?R? - Rif'an Fathoni; Siti A'isyah (Jurnal Penelitian Ilmiah INTAJ, 2020)
this study is a review of Islamic law regarding the problem of using unproductive waqf assets, thus giving rise to the practice of istibdal waqf. The data studied were the fatwas of the Shafi`iyyah scholars, namely Abu Ishaq as-Syairazi and Sheikh Zakaria al-Ansari and then compared them using content analysis techniques. This analysis aims to understand deeply and critically about the contents of the fatwa relating to the issue. The data used are generated from reading fiqh books, both classical and contemporary, focused on the fatwas contained in the works of the two scholars above. The data is collected and then used as a legal comparison. in legal istinb?th, both Zakaria al-Ansari and Abu Ishaq as-Syairazi followed Imam Shafi`i in the process of selecting the arguments as well as the methods used. In the discussion of istibd?l waqf, the argument used is the hadith narrated by Ibn Umar about waqf by Umar ibn Khattab and the provisions contained therein. However, there are differences in the fatwas given regarding istibdal waqf. According to al-Syairazi, if the waqf is a mosque, it is not allowed at all. Because it is still possible to pray or i`tik?f in it even though it is destroyed. But if it is non-mosques, there are two opinions: First, it cannot be for the same reason as a mosque. Second, it is permissible to sell and then use the money to buy the same waqf property, rather than letting it go to waste. Zakaria al-Ansari saw waqf cannot be replaced, either a mosque or a non-mosque. However, if there is a damaged mosque, there is a fear of collapsing, or there is a fear of vandalism, then it is possible to tear down the mosque and then rebuild the mosque, which is located near the first mosque, using the remains of the mosque that was torn down.